2013
DOI: 10.1371/journal.pone.0061172
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study Identifies Loci and Candidate Genes for Body Composition and Meat Quality Traits in Beijing-You Chickens

Abstract: Body composition and meat quality traits are important economic traits of chickens. The development of high-throughput genotyping platforms and relevant statistical methods have enabled genome-wide association studies in chickens. In order to identify molecular markers and candidate genes associated with body composition and meat quality traits, genome-wide association studies were conducted using the Illumina 60 K SNP Beadchip to genotype 724 Beijing-You chickens. For each bird, a total of 16 traits were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
97
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(112 citation statements)
references
References 38 publications
3
97
0
1
Order By: Relevance
“…In chickens, many genome-wide association studies (GWAS) were conducted using the Illumina 60K SNP Beadchip. Using this method, major loci associated with growth (Gu et al, 2011;Xie et al, 2012), egg production Wolc et al, 2012), rumpless and ear-tufted traits (Noorai et al, 2012), body composition and meat quality (Liu et al, 2013), resistance to Marek's disease (Li et al, 2013), and immune responses to Newcastle disease virus (Luo et al, 2013) were identified.…”
Section: Introductionmentioning
confidence: 99%
“…In chickens, many genome-wide association studies (GWAS) were conducted using the Illumina 60K SNP Beadchip. Using this method, major loci associated with growth (Gu et al, 2011;Xie et al, 2012), egg production Wolc et al, 2012), rumpless and ear-tufted traits (Noorai et al, 2012), body composition and meat quality (Liu et al, 2013), resistance to Marek's disease (Li et al, 2013), and immune responses to Newcastle disease virus (Luo et al, 2013) were identified.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies have been used to comprehensively analyze complex, economically important traits using technical statistical tools (Fan et al, 2011;Liu et al, 2011;Onteru et al, 2012;Liu et al, 2013;Wolc et al, 2014). Thus, GWAS have been one of the most effective approaches for identifying related QTLs and functional genes (Xu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, GWAS have been one of the most effective approaches for identifying related QTLs and functional genes (Xu et al, 2013). In chickens, Sun et al (2013) identified 14 new genes related to meat quality traits in chicken using a GWAS. Liu et al (2013) found that a consistent region on chicken GGA4 was associated with carcass weight and eviscerated weight.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several quantitative trait loci (QTLs) have been investigated in different chromosomal regions of chicken for the BW (Kerje et al, 2003;Pinard-van der Laan et al, 2009), CW , and TMW (Nones et al, 2006) traits. A few genome wide association studies (GWAS) have also identified several loci on chromosomes 1 and 4 that are strongly associated with BW, CW, EW, BMW, and TMW traits (Gu et al, 2011;Xie et al, 2012;Liu et al, 2013) in chicken. However, a limited number of genetic markers invested on chromosome 3 either by QTL or GWAS for growth traits in chicken.…”
Section: Introductionmentioning
confidence: 99%